SPEAKING ABOUT STORIES OF V.STEFANYK: WRITERS’ WORKS IN THE SCHOOL - Lavrusevych, N. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the peculiarities of the conducting extra-curricular reading lessons on the poems in prose V. Stefanyk’s in senior forms or the secondary school.